ANALISIS HASIL PENYELIDIKAN TANAH “PLATE BEARING TEST” UNTUK PENENTUAN PARAMETER DISAIN PONDASI (Studi Kasus Lokasi Rencana Pembangunan PLTU Jawa Barat) - RENA MISLINIYATI (Inersia: Jurnal Teknik Sipil, 2019)
Planning the design of building foundations depend on the results of soil investigation. Soil parameters used in the foundation design can be obtained from the results of ground investigation field or laboratory testing. Field investigation of soil that are commonly used to study the behavior and deformation of elastic stiffness and undrained shear strength is the Plate Bearing Test. In this research, soil investigation by Plate Bearing Test and interpretation of the results of investigations done to determine foundation design parameters of power plant building in West Java. Investigations carried out on three-point spread in the location of power plant . the results of plate bearing test are load-settlement curves. Then, analysis of parameters of the investigation done to obtain design parameters of power plant building foundations. The results showed that the subgrade modulus, elastic modulus and undrained shear strength at each point varies with the range of values are 994.77 ton/m3 to 1634.49 ton/m3, 297.57 ton/m3 to 488.94 ton/m2, 0.22 ton/m2 to 0.66 ton/m2. It can be concluded occur inconsistency of subgrade layer at this location. The results of this investigation can then be used as foundation design parameters in the planning of power plant building. For a more conservative design, soil parameters with the smallest value can be used as foundation design parameters.